Optimized Plant Productivity by evaluating the Performance and Capacity of the Primary Channel at the Irrigation Area (I.A.) Jeuram In Nagan Raya Regency - Hasdanita, Fitry; Nasution, Anisah; Masrura, Delfian; Safriani, Meylis (ASTONJADRO, 2025)
The development and improvement of irrigation infrastructure serve as the primary source of water supply during the growing season, which can significantly enhance agricultural production. This research aims to evaluate the performance of irrigation systems and the capacity of irrigation channels, this is essential to minimize water loss during the distribution of irrigation water, ensuring that the water needs of rice fields are met and optimizing crop productivity. The research was conducted in Irrigation Area (I.A) Jeuram. This research method is carried out by inventorying the existing conditions of physical and non-physical infrastructure. Then, was evaluates of irrigation area performance, based on the irrigation performance index. The hydraulic analysis to evaluate the channel using HEC-RAS software. The performance of the physical infrastructure of I.A. Jeuram is 26.38% of the optimal condition is 35%. This condition is categorized as moderately to severely damaged. Crop productivity stands is 9.64% of the optimal level of 12.5%. The overall performance index of I.A. Jeuram is 59.32% of its optimal condition, which is 77.5%, indicating that it is in desperate need of attention. While the primary channels can still accommodate the required discharge, its condition is also classified as moderately to severely damaged, compounded by issues of uncontrolled sedimentation. The physical and non-physical infrastructure adversely affects crop productivity and the overall service area of the Jeuram irrigation region. Therefore, it is essential to initiate repairs and ensure regular or periodic operation and maintenance of the irrigation system.